2008
DOI: 10.1093/protein/gzn049
|View full text |Cite
|
Sign up to set email alerts
|

Facile, reagentless and in situ release of Escherichia coli intracellular enzymes by heat-inducible autolytic vector for high-throughput screening

Abstract: In an effect to broaden the application of the heat-inducible autolytic vector pUC18-cI857/p(R)-SRRz-rrnB previously developed, a new vector pUC18-cI857/p(R)(T41C)-SRRz-rrnB (pEAS-1b) was quantitatively characterized under various growth temperatures, heat induction temperatures and durations, and IPTG (isopropyl beta-d-thiogalactoside) induction times, after resolving its erratic lysis profile found previously. Escherichia coli BL21 cells harboring this vector grew well at temperatures <36 degrees C, and lyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…Generally, the extracellular level of ␤-galactosidase, a native cytoplasmic protein, is considered an indication of cell lysis (24,25). In the present study, it was found that, at 22 h postinduction, the percentages of ␤-galactosidase activity in the culture medium were similar in cells expressing cutinase NS , cells expressing inactive cutinase NS S130A, and control cells.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…Generally, the extracellular level of ␤-galactosidase, a native cytoplasmic protein, is considered an indication of cell lysis (24,25). In the present study, it was found that, at 22 h postinduction, the percentages of ␤-galactosidase activity in the culture medium were similar in cells expressing cutinase NS , cells expressing inactive cutinase NS S130A, and control cells.…”
Section: Discussionsupporting
confidence: 62%
“…Cell lysis was determined as the percentage of extracellular enzyme activity versus the sum of extracellular and intracellular activities, using ␤-galactosidase as the reporter protein (24,25). Standard ␤-galactosidase activity was assayed according to the previously reported method (26).…”
Section: Cell Lysis Determinationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cloning junctions and cloned sequences were confirmed by sequencing of isolated plasmid DNA (Aokeding, China; or alternatively Invitrogen, China). The Lambda lysis system comprising the SRRz genes was amplified from the plasmid pEAS-1a (Xu et al 2006;Cai et al 2008) using the primers P1 and P2 (all primer sequences are listed in Table S1) and integrated using Gibson assembly into the standard part plasmid pSEVA331 (Silva-Rocha et al 2013;Durante-Rodríguez et al 2014) which was linearised via amplification using primers P3 and P4. The mutation S107 M3L and a standard part ribosome binding site (BBa_B0029; Jason Kelly, iGEM2006_MIT group) were provided on primer P1, whereas 13 bp of the native ribosome binding site of the chloramphenicol acetyltransferase (CAT) resistance gene was left in place before its coding sequence (CDS).…”
Section: Vector Constructionmentioning
confidence: 99%
“…While this approach is relatively straight-forward and great progress has been made in miniaturisation and maintaining control over potentially lethal leaky expression in such systems on the laboratory scale (Xu et al 2006;Cai et al 2008), practical applications are likely to fail in industrial settings due to the fact that autolysis needs to be induced during the very last process step, and cells grown to a high cell density are very poorly responsive to induction (Gefen et al 2014).…”
Section: Introductionmentioning
confidence: 99%